A Multivariate Interpretation of the Spanish-Language NIH Toolbox Cognition Battery: The Normal Frequency of Low Scores. (30th July 2021) - Karr, Justin E; Mindt, Monica Rivera; Iverson, Grant L
Abstract: Objective: The current study involved the preparation of multivariate base rates for the Spanish-language NIH Toolbox Cognition Battery (NIHTB-CB) based on the U.S. normative sample, quantifying the normal frequency of low scores among healthy adults. Method: Participants included 250 healthy Latinx adults ( M  = 38.8 ± 13.7 years old, range: 19–80; 72.0% women; education: M  = 11.5 ± 3.9 years) who completed the full Spanish-language NIHTB-CB, including two tests of crystallized cognition and five tests of fluid cognition. Multivariate base rates quantified the frequency at which participants obtained 1 or more fluid scores ≤25th, ≤16th, ≤9th, ≤5th, and ≤2nd percentile, per age-adjusted or demographically adjusted (age, gender, education) normed scores. Results: A substantial minority of participants had 1 or more low scores (e.g., 40.4% had 1 or more age-adjusted score ≤16th percentile). The frequencies of low scores increased with fewer years of education and lower crystallized cognitive ability. Higher frequencies of low scores were observed among participants who were born and educated abroad, versus within the USA; monolingual Spanish speakers, versus bilingual Spanish/English speakers; and from households below the national median income, versus households above the national median. Conclusion: Low scores were common and related to crystallized ability, education, and sociocultural variables. Although using demographically adjusted scores reduced group differences related to sociocultural variables, group differences were not eliminated, indicating that age, gender, and education score adjustments do not fully explain the associations between sociocultural variables and test performances. These stratified base rates may be useful when working with Spanish-speaking patients with diverse sociocultural characteristics.